Optical and Structural Characterization of Nickel Coatings for Solar Collector Receivers - Stefano Pratesi; Elisa Sani; Maurizio De Lucia (International Journal of Photoenergy)
The development of spectrally selective materials is gaining an increasing role in solar thermal technology. The ideal spectrally selective solar absorber requires high absorbance at the solar spectrum wavelengths and low emittance at the wavelengths of thermal spectrum. Selective coating represents a promising route to improve the receiver efficiency for parabolic trough collectors (PTCs). In this work, we describe an intermediate step in the fabrication of black-chrome based solar absorbers, namely, the fabrication and characterization of nickel coatings on stainless steel substrates. Microstructural characteristics of nickel surfaces are known to favorably affect further black chrome deposition. Moreover, the high reflectivity of nickel in the thermal infrared wavelength region can be advantageously exploited for reducing thermal emission losses. Thus, this report investigates structural features and optical properties of the nickel surfaces, correlating them to coating thickness and deposition process, in the perspective to assess optimal conditions for solar absorber applications.